(untitled) (Journal of International Studies, 2020)
In 1999, 2000, 2001, and 2002 the Indonesian Constitution of 1945 was amended by "Maje/is Permusyawaratan Rakyat" (MPR) or the Peoples’ Consultative Assembly, the bearer of the Peoples’ sovereignty. The amendments were not without opposition. A number of ex-military generals, political elites, and scientists opposed the amendments. They demanded that the amendments be cancelled and that the Peoples’ Consultative Assembly re-enact the Constitution of 1945 purely and consistently. Convinced by arguments that the Constitution had conceptual weaknesses, the majority of the Peoples’ Consultative Assembly insisted on amending the Constitution in order to make it more democratic, modern, comprehensive, and responsive to new challenges. It was also meant to implement the values and ideals formulated by the Preamble and to prevent the power holders from abusing their power and to improve the system of "checks and balances" in the power system. Further the amendments were made necessary to return back the sovereignty to the people; to confine the power and authority of the Peoples’ Consultative Assembly as well as the President, and enforce the power and authority of the Peoples’ Representative Council; to promote autonomy in the local governments; to establish the Regional Representative Council, the Judicial Commission as well as the Constitution Court; to guarantee human rights; to improve the quality of education; etc. And, in order to show that the amendments would not deviate from the basic values formulated in the Preamble, the Peoples’ Consultative Assembly decided not to touch at all the Preamble and to defend the form of the unitary state of the Republic of Indonesia.